HUBUNGAN PENERAPAN MEDIA PEMBELAJARAN E-LEARNING DENGAN METODE PEMBELAJARAN BERBASIS PENUGASAN TERHADAP HASIL BELAJAR MAHASISWA TEKNIK OTOMOTIF PADA KULIAH TEKNOLOGI ALAT BERAT - Wagino Wagino; M.Riki Rinaldi; Dwi Sudarno Putra; Ahmad Arif (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
All in-person learning has been replaced with online learning as a result of the Covid-19 pandemic in Indonesia. During the Covid-19 emergency, this aims to fulfill students' rights to obtain education-related services. In the Heavy Equipment Technology course, the purpose of this study is to determine whether assignment-based learning and the use of e-learning media can improve student learning outcomes. In this study, correlational quantitative research of this kind was used. From a total of 124 students, 55 were selected at random. SPSS version 20 is used for analysis in this study, and Windows 10 is used to enter data. The research data for variable (X) account for 94.3 percent of the total. The variable (Y) is included in the very good category for 92.7 percent of the research data. Rcount 0.384 > Rtable 0.261 were the positive category results from correlation theory testing. The t test shows a positive correlation between the application of e-learning learning media and assignment strategies (Tcount 1.906 > Ttable 1.673). The findings demonstrated that the variable of instructional media application with assignment-based learning contributed 13.1%, while other variables influenced 86.9%.Keywords: e learning, Assignment Learning Methods, Learning Results.